Vertrauen in Roboter und dessen Beeinflussbarkeit durch sprachliches Framing Eine empirische Untersuchung der Interaktion mit Cobots am Arbeitsplatz - Kopp, Tobias (KIT Scientific Publishing, 2022)
Collaborative robots (cobots) enable human-robot interactions in the workplace without safety fences. An appropriate level of trust by employees is critical to the success of these interactions. Anthropomorphic perceptions and fears of technological replacement affect trust formation. They can be influenced by linguistic framing, as this interdisciplinary empirical study shows.